Exploring The Legacy: The Biological Interactions of Bis Schiff Bases and Their Coordinated Azomethine Derivatives Over Time - Zahid Khan; M. Asad K. Tanoli (ziauddin University, 2024)
Schiff base class of compounds has a double bond between carbon and nitrogen. They form a carbonyl molecule, like an aldehyde or ketone, when combined with a primary amine. A Schiff base is structurally an aldehyde or ketone's nitrogen counterpart where the carbonyl group (CO) has been replaced with an imine or azomethine group. Schiff bases are a significant class of organic compounds with potential applications in many biological fields. They are best recognized for their capacity to generate transition metal complexes. Schiff-base ligands are easily produced and can form complexes with almost any metal ion. The main focus of this review is on the bis Schiff bases, a subclass of Schiff bases identified by the occurrence of two azomethine groups in their structures. These azomethine groups are major contributors to the activity of these compounds, along with substituent effects on key positions. For scientists interested in learning about these particular compounds' potential for specific biological uses, this article provides literature examples of the compounds in question and their biological action processes. A review focusing on the biological applications of Schiff base-derived ligands and their complexes is essential due to the numerous recent publications detailing their antibacterial, antioxidant, and enzyme-inhibitory activities.